2021
DOI: 10.4314/njb.v37i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Extended Spectrum Beta-Lactamases (ESBLs)-Producing Escherichia Coli Isolated From UTI Patients Attending some Selected Hospitals In Minna, Nigeria

Abstract: Globally, urinary tract infections are one of the most common infections in need of urgent clinical attention. The prevalence of extended spectrum beta-lactamases (ESBL)- producing Escherichia coli isolated from urine samples of some UTI patients and s of apparently healthy individuals in Minna, Nigeria, is investigated. Standard microbiological techniques were used to conduct this study. A total of 170 catch midstream urine samples submitted to the Medical Microbiology Laboratories of 4 different hospitals (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…3 A study on typhoid among young children, 4 stressed the need for careful monitoring of antimicrobial resistance in a view to prevent increase of resistance strains and resultant infections to vulnerable communities. Diarrheagenic E. coli has demonstrated a significant resistance to beta lactams antibiotics that are commonly prescribed, 5 with contributing factors to diarrhea cases attributed to poor quality of foods, poor water systems, lack of proper hygiene often due to lack of water and poor sanitation. Studies have shown that human and animal waste are the main sources of contamination on the environment that hosts strains that are antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…3 A study on typhoid among young children, 4 stressed the need for careful monitoring of antimicrobial resistance in a view to prevent increase of resistance strains and resultant infections to vulnerable communities. Diarrheagenic E. coli has demonstrated a significant resistance to beta lactams antibiotics that are commonly prescribed, 5 with contributing factors to diarrhea cases attributed to poor quality of foods, poor water systems, lack of proper hygiene often due to lack of water and poor sanitation. Studies have shown that human and animal waste are the main sources of contamination on the environment that hosts strains that are antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%